Kompetensi Kepribadian Guru Prespektif KH Hasyim Asy’ari Dalam Kitab Adabul Alim Wal Muta’allim - Taufiqurrahman Taufiq; Maftuhah Maftuhah; Zahruddin Zahruddin; Annisa Nabilah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
The purpose of this study was to determine the personality competence of KH Hasyim Asy'ari's perspective teacher and its relevance to current education. The teacher's personal competence is the main requirement for carrying out his duties as an educator. Competence must be owned by the teacher because the teacher will meet various kinds of student characters, the teacher's task is to improve the character and morals of students. The method used in this study is a qualitative type of library (library research), namely the type of research that refers to the treasures of literature such as books, articles and e-journals. The results showed that personality competencies according to KH Hasyim Asy'ari were: straightening intentions (intent to seek Allah's blessing), motivators, loving students, making it easier for students to understand lessons, enthusiastic when teaching and mastering various teaching methods, evaluation, mentorship, behaving the same to all students, monitoring the behavior of students, the teacher behaves well towards students, the teacher provides assistance to students, the teacher pays attention to the presence of students, is humble before students, and speaks kind words to students. Besides that, there is also harmony between the adabul alim wa wal muta'alim book and Permendiknas no 14 of 2005 concerning teacher personality. The elucidation of Article 10 paragraph (1) teacher's personal competence includes: solid personality, noble, wise and authoritative as well as being a role model for students.